Pietà – Jungfru Marias sorg och Kristi död i svensk medeltid - Ann-Catrine Eriksson (Kulturella Perspektiv, 2013)
The Pietà was introduced in Swedish medieval art during the late fourteenth century and this article is focussing on its expressions of grief and death. The popularity of the Pietà can be explained by the historical context (the Black Death and the Hundred Years War), hard times that made death and despair extremely present, connected to sin, and a common experience for all no matter of social hierarchies. Virgin Mary is a vital part in the Pietà as she is both an intercessor for humans who wants forgiveness for their sins and the voice of her son’s message since he can speak no more. It is through her story, experience and grief that humans can both understand and find the merciful love Christ has promised after death that will guarantee eternal life in Heaven.